PELATIHAN PRAKTIS AKUNTANSI: PENINGKATAN KETERAMPILAN MANAJEMEN KEUANGAN BERBASIS TEKNOLOGI INFORMASI PADA UMKM BUMDesa PULE SEJAHTERA - Kartikasari, Evi dwi; Rodhiyah, Ma’rufatur; Khotiah, Titik; Wiyanti, Melisa Yuli; Romadhon, Muhammad Farih (Jurnal Abdi Insani, 2024)
The problems that exist in MSMEs in Pule Village based on an initial survey stated that less than 5% of MSME actors utilize information systems and there are approximately 4% of MSME actors who document their financial management. 92% of MSME actors in Pule Village are lay people who do not come from an Economic Education background so that their ability in financial literacy and managerial management skills are very minimal. So far, MSME managers have only focused on the sale of the products produced without calculating the estimated expected profit. This is a challenge for Accounting Academics to provide insight and training on information technology-based financial management so that the existence of MSMEs can achieve maximum goals. It is hoped that MSMEs in Pule Village will be able to become independent and rapidly developing MSMEs through additional working capital and skills in preparing good financial reports and being able to utilize information technology as a means of supporting activities. This service is carried out using the Community Development method, namely an approach that is oriented towards developing community empowerment by making the community the subject, object of development, and direct involvement in various service activities that will be carried out. The results of this service have a positive and significant impact. The increase in partners' accounting literacy has increased and the ability to prepare financial reports has increased by 80%. It is hoped that this service can become a community service that is continued, meaning that there is monitoring and assistance for partners to continuously implement the results of technology and innovation provided in community service activities.